Facile synthesis of highly conductive sulfur-doped reduced graphene oxide sheets. Issue 2 (11th December 2015) - Tian, Zhengshan; Li, Jitao; Zhu, Gangyi; Lu, Junfeng; Wang, Yueyue; Shi, Zengliang; Xu, Chunxiang
Abstract : A facile hydrothermal reaction process was designed to synthesize sulfur-doped RGO sheets with excellent conductivity. Abstract : A facile hydrothermal strategy to synthesize sulfur-doped reduced graphene oxide (S-RGO) sheets with good conductivity is proposed by using only graphene oxide (GO) sheets and sodium sulphide (Na2 S) as precursors through a hydrothermal reaction process at 200 °C in one pot. The introduced Na2 S can act as not only a sulfur dopant, but also as a highly efficient reducing agent in the formation of S-RGO sheets, which dramatically improves the electrical conductivities of the resulting S-RGO sheets compared with previous reports. The current reaches about 50.0 mA at an applied bias of 2.0 V for the optimized sample with 2.22 at% sulfur doping. This current value is much higher than that of RGO sheets (∼1.2 mA) annealed at 200 °C, and very close to that of single-layer graphene sheets (∼68.0 mA) prepared using chemical vapor deposition under the same test conditions. The resulting highly conductive S-RGO sheets offer many promising technological applications such as efficient metal-free electrocatalysts in oxygen reduction reactions in fuel cells and as supercapacitor electrode materials for high-performance Li-ion batteries.